Advertisement Remove all ads

(X Plus 3)Square Root 2 – 4(X + 3) – 5 = 0 - Mathematics

(x + 3)² – 4(x + 3) – 5 = 0

Advertisement Remove all ads

Solution

`(x + 3)^2 - 4(x + 3) - 5 = 0`

Let  x + 3 = y

then `y^2 - 4y - 5 = 0`

`=> y(y - 5) +1(y -5)= 0`

if y - 5 =    0 or y + 1 = 0

then y = 5 or y = -1

=> x +  3 = 5 or x + 3 = -1

=> x = 2 or x = -4

  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×